Whose Expertise Is It? Evidence for Autistic Adults as Critical Autism Experts - Gillespie-Lynch, Kristen; Kapp, Steven K.; Brooks, Patricia J.; Pickens, Jonathan; Schwartzman, Ben (Frontiers in Psychology, 2017)
Autistic and non-autistic adults’ agreement with scientific knowledge about autism, how they define autism, and their endorsement of stigmatizing conceptions of autism has not previously been examined. Using an online survey, we assessed autism knowledge and stigma among 636 adults with varied relationships to autism, including autistic people and nuclear family members. Autistic participants exhibited more scientifically based knowledge than others. They were more likely to describe autism experientially or as a neutral difference, and more often opposed the medical model. Autistic participants and family members reported lower stigma. Greater endorsement of the importance of normalizing autistic people was associated with heightened stigma. Findings suggest that autistic adults should be considered autism experts and involved as partners in autism research.